Prevalence and Associated Characteristics of HIV-Infected Children in Latin America Who Know Their HIV Status. (14th February 2017) - Lee, Sonia; Siberry, George K; Alarcón, Jorge O; Vega, Mary Reyes; Roca, Lenka Kolevic; Gutierrez, César; Celia de Menezes Succi, Regina; Ferreira Peixoto, Mario; Stoszek, Sonia K; Hazra, Rohan; Harris, D Robert
Abstract: We estimated the prevalence of human immunodeficiency virus (HIV) disclosure in children from a prospective observational cohort study conducted at clinical sites in Brazil, Mexico, and Peru. Fewer than half of the children in this study knew their HIV status, which highlights the need for better strategies for disclosure that are age and culturally appropriate.